Attenuated stress‐evoked anxiety, increased sucrose preference and delayed spatial learning in glucocorticoid‐induced receptor‐deficient mice. (27th November 2012) - E. Vollmer, L.; Ghosal, S.; A. Rush, J.; R. Sallee, F.; P. Herman, J.; Weinert, M.; Sah, R.
Abstract : The glucocorticoid‐induced receptor (GIR) is a stress‐responsive gene that is abundantly expressed in forebrain limbic regions. Glucocorticoid‐induced receptor has been classified as a Neuropeptide Y‐like receptor, however, physiological attributes have not been investigated. In this study, mice lacking GIR (−/−) were screened in various paradigms related to stress, anxiety, activity, memory, fear and reward. GIR −/− mice elicited behavioral insensitivity to the anxiogenic effects of restraint stress. However, hypothalamic pituitary adrenal axis response to stress was not impacted by GIR deficiency. Increased preference for sucrose was observed in GIR −/− mice suggestive of modulation of reward‐associated behaviors by the receptor. A delayed acquisition of spatial learning was also observed in GIR −/− mice. There were no effects of genotype on the modulation of anxiety‐like behavior, activity, fear‐conditioning and extinction. Our data extend previous studies on GIR regulation by glucocorticoids and provide novel evidence for a role of GIR in reward, learning and the behavioral outcomes of stress . Abstract : The glucocorticoid induced receptor regulates spatial learning, reward and behavioral consequences of stress exposure.